Dora climbs Star Mountain - Inches, Alison; A&J Studios (London : Simon Schuster/Nick Jr., 2007)
Dora and Boots climb Star Mountain in search of the necklace her grandmother gave her.
"Based on the TV series Dora the Explorer as seen on Nick Jr."--T.p. verso.
1.6
K-3
Text mainly in English with some Spanish words.
Keywords: Adventure and adventurers -- Fiction; Dora the Explorer (Fictitious character) -- Fiction; Explorers -- Fiction; Girls -- Fiction; Monkeys -- Fiction; Adventure fiction; Dora the Explorer (Fictional character) -- Fiction; Explorers -- Fiction; Girls -- Fiction; Monkeys -- Fiction